Magnetic Alignment of Electrospun Fiber Segments Within a Hydrogel Composite Guides Cell Spreading and Migration Phenotype Switching - Hiraki, Harrison L.; Matera, Daniel L.; Rose, Michael J.; Kent, Robert N.; Todd, Connor W.; Stout, Mark E.; Wank, Anya E.; Schiavone, Maria C.; DePalma, Samuel J.; Zarouk, Alexander A.; Baker, Brendon M. (Frontiers in Bioengineering and Biotechnology, 2021)
Fibrous extracellular matrix (ECM) proteins provide mechanical structure and adhesive scaffolding to resident cells within stromal tissues. Aligned ECM fibers plays an important role in directing morphogenetic processes, supporting mechanical loads, and facilitating cell migration. Various methods have been developed to align matrix fibers in purified biopolymer hydrogels, such as type I collagen, including flow-induced alignment, uniaxial tensile deformation, and magnetic particles. However, purified biopolymers have limited orthogonal tunability of biophysical cues including stiffness, fiber density, and fiber alignment. Here, we generate synthetic, cell-adhesive fiber segments of the same length-scale as stromal fibrous proteins through electrospinning. Superparamagnetic iron oxide nanoparticles (SPIONs) embedded in synthetic fiber segments enable magnetic field induced alignment of fibers within an amorphous bulk hydrogel. We find that SPION density and magnetic field strength jointly influence fiber alignment and identify conditions to control the degree of alignment. Tuning fiber length allowed the alignment of dense fibrous hydrogel composites without fiber entanglement or regional variation in the degree of alignment. Functionalization of fiber segments with cell adhesive peptides induced tendon fibroblasts to adopt a uniaxial morphology akin to within native tendon. Furthermore, we demonstrate the utility of this hydrogel composite to direct multicellular migration from MCF10A spheroids and find that fiber alignment prompts invading multicellular strands to separate into disconnected single cells and multicellular clusters. These magnetic fiber segments can be readily incorporated into other natural and synthetic hydrogels and aligned with inexpensive and easily accessible rare earth magnets, without the need for specialized equipment. 3D hydrogel composites where stiffness/crosslinking, fiber density, and fiber alignment can be orthogonally tuned may provide insights into morphogenetic and pathogenic processes that involve matrix fiber alignment and can enable systematic investigation of the individual contribution of each biophysical cue to cell behavior.